2015
DOI: 10.1039/c4ay02287d
|View full text |Cite
|
Sign up to set email alerts
|

Towards on-site testing of Phytophthora species

Abstract: Rapid detection and accurate identification of plant pathogens in the field is an ongoing challenge. In this study, we report for the first time on the development of a helicasedependent isothermal amplification (HDA) in combination with on-chip hybridization for the detection of selected Phytophthora species. The HDA approach allows the efficient amplification of the yeast GTP-binding protein (Ypt1) target gene region at one constant temperature in a miniaturized heating device. The assay's specificity was de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(14 citation statements)
references
References 49 publications
0
14
0
Order By: Relevance
“…In order to improve the detection and achieve a putative in- field application, novel isothermal amplification techniques could be implemented. 51,52 Moreover, the SERS-based DNA detection, relying on DNA-DNA-hybrid formation, could be performed in a handheld Raman device, that allows the applicability at the point-of-need due to its portability. In summary, a reliable, reproducible and thermally stable SERS assay has been developed for the detection of specific DNA hybridization between immobilized capture probes and the sequence-matching target DNA.…”
Section: Discussionmentioning
confidence: 99%
“…In order to improve the detection and achieve a putative in- field application, novel isothermal amplification techniques could be implemented. 51,52 Moreover, the SERS-based DNA detection, relying on DNA-DNA-hybrid formation, could be performed in a handheld Raman device, that allows the applicability at the point-of-need due to its portability. In summary, a reliable, reproducible and thermally stable SERS assay has been developed for the detection of specific DNA hybridization between immobilized capture probes and the sequence-matching target DNA.…”
Section: Discussionmentioning
confidence: 99%
“…Another advantage of the electrochemical approach is the independence from background light or sample color, even though electrochemically active samples may influence the readout. Examples of portable devices for the electrochemical detection of amplified DNA from plant pathogens are already available (Julich et al, 2011;Schwenkbier et al, 2014Schwenkbier et al, , 2015a. The method exploits the enzymatic-triggered silver deposition on the electrode to read the signal both visually and electrochemically.…”
Section: Detection Methodsmentioning
confidence: 99%
“…Septa allow the sterile injection of fluid samples and reagents, and data were collected through the integration of an electrical readout. A similar approach was used for the detection of selected Phytophthora species [ 88 ], with the development of a helicase-dependent isothermal amplification (HDA) in combination with on-chip hybridization, employing silver nanoparticles as label and enabling both visual detection and electrical readout. The study showed a successful application in amplifying isolated template DNA from Phytophthora cultures and infected plant material.…”
Section: Innovative Technologies For Plant Pathologymentioning
confidence: 99%